ANALYSIS OF PRO-POOR GROWTH ON POVERTY IN SOUTH SUMATRA - Cristover, Daniel; Satriani, Jeanne Aleysia; Siregar, Anandhita; Natasyha, Zaskia Kurnia (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2025)
Poverty plays a critical role in shaping the economic development of a region, as it directly affects income distribution and access to resources. In South Sumatra, for example, while poverty declined from 2017 to 2022, the region’s economic growth showed signs of stagnation. The Gini coefficient, which measures income inequality, remained largely unchanged during this period, raising concerns about the inclusivity of the growth. This paradox prompted the author to conduct a study to explore the relationship between economic growth and poverty alleviation in South Sumatra and to determine whether the region's growth could be classified as